Ribavirin inhibits human parainfluenza virus type 2 replication in vitro. (November 2014) - Kihira, Sahoko; Uematsu, Jun; Kawano, Mitsuo; Itoh, Ai; Ookohchi, Ayumi; Satoh, Saemi; Maeda, Yurie; Sakai, Kae; Yamamoto, Hidetaka; Tsurudome, Masato; O'Brien, Myles; Komada, Hiroshi
Abstract The antiviral activities of eight nucleoside analog antiviral drugs (ribavirin, acyclovir, lamivudine, 3′‐azido‐3′‐deoxythymidine, emtricitabine, tenofovir, penciclovir and ganciclovir) against human parainfluenza virus type 2 (hPIV‐2) were investigated. Only ribavirin (RBV) inhibited both cell fusion and hemadsorption induced by hPIV‐2. RBV considerably reduced the number of viruses released from the cells. Virus genome synthesis was inhibited by RBV, as determined by real time PCR. An indirect immunofluorescence study showed that RBV largely inhibited viral protein synthesis. mRNAs of the proteins were not detected, indicating that inhibition of protein synthesis was caused by transcription inhibition by RBV. Using a recombinant green fluorescence protein‐expressing hPIV‐2 without matrix protein, it was found that RBV did not completely inhibit virus entry into the cells; however, it almost completely blocked multinucleated giant cell formation. RBV did not disrupt actin microfilaments and microtubules. These results indicate that the inhibitory effect of RBV is caused by inhibition of both virus genome and mRNA synthesis, resulting in inhibition of virus protein synthesis, viral replication and multinucleated giant cell formation (extensive cell‐to‐cell spreading of the virus).